2021
DOI: 10.1093/cvr/cvab094
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular RNA markers and artificial intelligence may improve COVID-19 outcome: a position paper from the EU-CardioRNA COST Action CA17129

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has been as unprecedented as unexpected, affecting more than 105 million people worldwide as of February 8th, 2020 and causing more than 2.3 million deaths according the World Health Organization. Not only affecting the lungs and provoking acute respiratory distress, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is able to infect multiple cell types including cardiac and vascular cells. Hence a significant proportion of infected patients develop c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 118 publications
0
16
0
Order By: Relevance
“…This paper, however, overlooks one crucial aspect: the paradoxical role of platelets in the setting of MI. Activated platelets, beyond promoting arterial thrombus formation, may contribute to cardiac damage via different mechanisms, including the formation of coronary microvascular microthrombi, induction of platelet-leukocyte interactions, release of vasoconstrictor molecules (e.g., thromboxane A2), and (microRNA-containing) microvesicles [ 4 , 9 ]. However, increasing evidence supports the notion that platelets also carry and release multiple factors with the potential to reduce rather than promote IR injury (Fig.…”
mentioning
confidence: 99%
“…This paper, however, overlooks one crucial aspect: the paradoxical role of platelets in the setting of MI. Activated platelets, beyond promoting arterial thrombus formation, may contribute to cardiac damage via different mechanisms, including the formation of coronary microvascular microthrombi, induction of platelet-leukocyte interactions, release of vasoconstrictor molecules (e.g., thromboxane A2), and (microRNA-containing) microvesicles [ 4 , 9 ]. However, increasing evidence supports the notion that platelets also carry and release multiple factors with the potential to reduce rather than promote IR injury (Fig.…”
mentioning
confidence: 99%
“…NcRNAs are transcribed by either RNA polymerase I, II or III, depending on the individual ncRNA [14] . According to their lengths, they can be divided into two main groups: (1) small or short ncRNAs including microRNAs (miRNAs), small interfering RNAs (siRNAs), PIWI-interacting RNA (piRNA) and small nucleolar RNAs (snoRNAs); and (2) long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) [15] . A rapidly growing number of studies has unravelled associations between aberrant ncRNA expression and human diseases.…”
Section: Epitranscriptomic Signature In the Brain-heart Axis Of Covid...mentioning
confidence: 99%
“…A rapidly growing number of studies has unravelled associations between aberrant ncRNA expression and human diseases. NcRNAs have emerged as promising candidates for the treatment of a variety of diseases and play a potential significant role in host-virus interactions [15] . Dysregulated noncoding RNAs (ncRNAs) expression levels in lung tissue and liquid biopsies from COVID-19 patients indicate that ncRNAs may play an important role in the pathogenesis, and hence clinical outcomes of COVID-19.…”
Section: Epitranscriptomic Signature In the Brain-heart Axis Of Covid...mentioning
confidence: 99%
“…Apart from histone modifications and DNA methylation, non-coding RNA (nc-RNA) is an important contributor of epigenetic changes. In COVID-19, several nc-RNA are upregulated or downregulated which render them as potential biomarkers of the disease [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Askari et al reported that several long nc-RNAs and micro RNAs (mi-RNAs) are differentially expressed in COVID-19, some with specific observations in female versus male patients [ 46 ].…”
Section: Altered Epigenomic Signature Of Dna Methylation In Heart Imp...mentioning
confidence: 99%
“…Interestingly, nc-RNAs have significant roles in cardiac biology, including miR-29s and miR-30b reported in this study, which have anti-fibrotic roles in the heart and correlate with ischemic heart disease, respectively [ 46 ]. Badimon et al provides a comprehensive compilation of nc-RNAs, including miR-16-2-3p, lncRNA NEAT1 , which are upregulated in COVID-19 patients, and lncRNA DANCR , miR-183-5p, etc., which are downregulated [ 47 ]. Such differentially expressed nc-RNAa can serve as potential biomarkers of COVID-19.…”
Section: Altered Epigenomic Signature Of Dna Methylation In Heart Imp...mentioning
confidence: 99%